The Private and Social Benefits of Preparing for Natural Disasters. Issue 3 (November 2014) - Stein, Robert; Buzcu-Guven, Birnur; Dueñas-Osorio, Leonardo; Subramanian, Devika
In this paper we inquire about the consequences of preparing for hurricanes for individuals and the larger community. Are there collective action benefits from individual-level preparation activities; do the actions individuals take to prepare themselves for a pending hurricane have social benefits for the entire community? We identify shadow evacuations – persons evacuating from areas not designated for evacuation–as a significant social cost that might be mitigated by individual preparation for severe weather. We test our hypotheses with data from a survey conducted with residents of Harris County, Texas, after Hurricane Ike in 2008. We find that preparation has a negative effect on personal injury and property damage and that preparation has a significant and negative effect on the likelihood individuals evacuate, especially residents of non-evacuation areas (low risk areas). Our findings have strong implications on how emergency planners and local officials should prepare for and communicate with the public before severe weather episodes.